1994
DOI: 10.1017/s0003356100007674
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a hormonal preparation containing glucocorticoids (dexamethasone esters), progestagen (chlormadinone acetate) and oestrogen (ethinyl oestradiol) on testosterone, insulin-like growth factor-1 (IGF-1), IGF-binding proteins and spermatogenic cells in finishing bulls

Abstract: Growth-promoters are banned by the European Community, but different hormonal cocktails are still illegally used. This experiment was therefore conducted to evaluate the effects of one of the most currently used cocktails on some hormonal parameters and spermatogenesis in finishing bulls in an attempt to provide a suitable screening technique for their illegal use. Sixteen double-muscled Belgian White Blue finishing bulls (mean ivcight: 535 (s.d. 37) kg) were blocked into control (C; no. = 7) and treated (Dex;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The results of Sillence and Etherton (1991) and Miell et al (1993), both show elevated IGF-I by RIA. Also, Renaville et al (1994) observed no significant difference in plasma IGF-I levels (213 vs. 245 µg L -1 ).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The results of Sillence and Etherton (1991) and Miell et al (1993), both show elevated IGF-I by RIA. Also, Renaville et al (1994) observed no significant difference in plasma IGF-I levels (213 vs. 245 µg L -1 ).…”
mentioning
confidence: 65%
“…In the human, Miell et al (1993) demonstrated that dexamethasone in normal human volunteers significantly increases IGFBP-3 levels while IGFBP-2 levels decrease. A higher level of IGFBP-3 was also reported in bulls treated with dexamethasone esters given along with estrogen and progestagen (Renaville et al 1994).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…CORTICOSTEROIDS are used illegally in several countries as growth promoters in veal calves and beef production, in order to enhance carcase and meat quality traits (Renaville and others 1994, Gottardo and others 2008). These drugs are usually used in association with sex steroids and β‐agonists to obtain a higher proportion of lean meat (Meyer 2001).…”
mentioning
confidence: 99%
“…Various studies have been performed to assess the effects of non-therapeutic dexamethasone use on beef cattle growth and slaughter performance (Brethour, 1972;Dicke et al, 1974), while others (Renaville et al, 1994;Corah et al, 1995) also considered metabolic parameters and nutrient partitioning hormones. None of the abovementioned works considered cattle welfare, however, which is currently one of the most important issues for the consumer (McGlone, 2001).…”
Section: Introductionmentioning
confidence: 99%